Calcium-based material activation-based geopolymer and preparation method and coagulation time regulation and control method thereof
By using calcium-based materials to activate the ground polymer, the material ratio and temperature are adjusted, and the problem of difficult control of the settling time of the ground polymer under different temperature conditions is solved, stable settling time control within the temperature range of 5-50℃ is achieved, construction performance and application scenarios are improved, and low carbon emission targets are supported.
Patent Information
- Application Number
- CN202411974289.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The coagulation and hardening process of ground polymers is significantly affected by temperature, resulting in a prolonged settling time and low strength in low temperature environments, a shortened settling time and loss of material fluidity, making it difficult to regulate the coagulation time under different temperature conditions, affecting construction performance.
Using a calcium-based material-activated geopolymer, the coagulation time of the geopolymer is regulated by adjusting the weight percentage of calcium-based material A and calcium-based material B, combining the ratio of alkali trigger and metakaolin, the thermal relieving effect of calcium-based material A and the high hydration heat of calcium-based material B are used.
The settling time of the polymer is stably controlled within a wide temperature range (5-50℃), improving its applicability at different temperatures, ensuring construction performance, expanding application scenarios, and reducing production energy consumption, supporting low carbon emissions and sustainable development of the construction industry.
Smart Images

Figure BDA0005220074040000051 
Figure BDA0005220074040000052 
Figure BDA0005220074040000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of geopolymers, and in particular to a geopolymer which can be used for different ambient temperatures and is activated based on calcium-based materials, a preparation method thereof, and a method for regulating the setting time thereof. Background Art
[0002] Geopolymer is a new type of low-carbon material with excellent strength and acid and alkali resistance. Its carbon emissions during the production process are only 10% to 30% of ordinary Portland cement, so it is regarded as a "green" cement. At present, research on geopolymer is committed to its application in high-strength, fire-resistant, corrosion-resistant and highly durable building materials. However, the setting and hardening process of geopolymer is significantly affected by temperature, which in turn affects its mechanical properties. Under low temperature conditions, the setting time of geopolymer is significantly prolonged, and the strength develops slowly, and the final strength is low; while under high temperature conditions, the setting time is greatly shortened, the material fluidity is quickly lost, and the shrinkage caused by temperature strain affects the strength. Therefore, how to regulate the setting time of geopolymer under different temperature conditions to ensure its construction performance is the key to promoting the application of this material in more projects. There is currently no means to solve this problem.
[0003] In terms of preparing geopolymer materials suitable for different temperature scenarios, the patent "A geopolymer that hardens rapidly at room temperature and its preparation method" (CN105621911A) uses kaolin to be added to an alkali activator step by step and mixed and stirred to prepare the geopolymer, but the number of additions is large and the stirring time is long and it is only applicable to room temperature conditions; the patent "A geopolymer that hardens rapidly based on low temperature crystallization and its preparation method" (CN118307245A) proposes to prepare the geopolymer based on the crystallization principle of kaolin and alkali activator at low temperature, but it needs to be cured and formed at 20°C before it can be put into use in a low temperature environment; the patent "Metakaolin-slag-based geopolymer for oilfield cementing and its high-temperature retarder" (CN200810020859.3) proposes a geopolymer that can be prepared and used at high temperatures, but the material also has the characteristic of being only applicable to high temperatures. In summary, these patents have limitations on the use of geopolymers under different temperature conditions, cannot cover a large temperature range, and have a long setting time, which is not convenient for engineering applications. In addition, the implementation content of the above patent is only based on the material design of a specific mix ratio, and does not involve the calculation and optimization method of the polymer coagulation time under different temperature conditions. Summary of the invention
[0004] The purpose of the present invention is to provide a geopolymer that can be used at different ambient temperatures and is based on calcium-based material activation, a preparation method thereof, and a method for regulating its setting time. The aforementioned setting time regulation method utilizes the regulating properties of calcium-based materials A and B on the setting time of the geopolymer, improves the applicability of the geopolymer at different temperatures, and has a certain research reference value.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A geopolymer activated by calcium-based materials, wherein the geopolymer comprises, by weight percentage, 40-50% of metakaolin, 42-50% of an alkali activator, 2-10% of a calcium-based material A, and 2-8% of a calcium-based material B, and the sum of the weight percentages of the raw materials is 100%;
[0007] The method for preparing the geopolymer comprises the following steps:
[0008] 1) Stirring: Pour the metakaolin, calcium-based material A and calcium-based material B into a cement slurry mixer and stir at a low speed, pour the alkali activator during the low-speed stirring, then stir at a low speed until the mixture is uniform, and finally stir at a high speed to obtain a geopolymer slurry;
[0009] 2) Molding and curing: Pour the geopolymer slurry prepared in step 1) into a mold, vibrate on a vibration platform for 60 seconds, and place in a specified temperature environment for curing for 24 hours to obtain a geopolymer activated based on a calcium-based material.
[0010] Furthermore, the mesh size of the metakaolin is not less than 1250 meshes.
[0011] Furthermore, the alkaline activator comprises, by weight percentage, 70-72% of liquid water glass, 12-14% of solid sodium hydroxide and 16-18% of water, and the alkaline activator modulus is 1.4-1.6 when the solid sodium hydroxide is used to adjust the alkaline activator;
[0012] The preparation method of the base activator is:
[0013] a) preparing sodium hydroxide solution: mixing solid sodium hydroxide and water, stirring until a uniform transparent solution is obtained, and using the solution after the temperature drops to room temperature;
[0014] b) preparing an alkaline activator: mixing liquid water glass and the sodium hydroxide solution prepared in step a) and stirring them uniformly to obtain an alkaline activator.
[0015] Furthermore, the modulus of the liquid water glass is 3.1-3.3, and the solid content is 42.5%.
[0016] Furthermore, the calcium-based material A is high-calcium fly ash, and its components include: SiO2: 45-55wt%, Al2O3: 25-35wt%, CaO: 10-15wt%, and the rest are impurities; the calcium-based material B is one of calcium oxide and cement clinker, preferably calcium oxide.
[0017] Furthermore, in step 2), the site temperature environment is 5-50°C.
[0018] Furthermore, in step 1), the stirring speeds of the low-speed stirring and the high-speed stirring are 90-100 r / min and 250-260 r / min, respectively.
[0019] A method for controlling the setting time of a metakaolin polymer activated by a calcium-based material as described in any one of the above, the method for controlling the setting time comprises the following steps:
[0020] Step 1: Based on the selected initial raw material ratio, calculate the molar ratio of Na2O / Al2O3, i.e. According to the site temperature conditions, the average site temperature for 72 hours is obtained as the ambient temperature T;
[0021] Step 2: Substituting the ambient temperature T and the initial raw material ratio into the geopolymer setting time calculation formula, the setting time of the geopolymer activated by the calcium-based material is calculated, and the setting time includes the initial setting time and the final setting time;
[0022] Step three: Compare the initial setting time and final setting time calculated in step two with the initial setting time and final setting time required for construction. If they do not meet the construction requirements, adjust the weight percentage of calcium-based material A and calcium-based material B based on the geopolymer setting time calculation formula, correct the setting time, make the setting time meet the construction requirements, and prepare a kaolin geopolymer based on calcium-based material activation suitable for the current ambient temperature T according to the optimized raw material ratio.
[0023] Furthermore, in step 2, the formula for calculating the setting time of the geopolymer is:
[0024] Initial setting time:
[0025] Final setting time:
[0026] Wherein: CaA is the weight percentage of calcium-based material A; CaB is the weight percentage of calcium-based material B.
[0027] Furthermore, in step three, the construction requires an initial setting time of 45-120 minutes and a final setting time of 120-360 minutes.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention provides a technical method that can stably control the setting time of geopolymers over a wide temperature range. Compared with the prior art, which is only applicable to room temperature or specific temperature conditions, the present invention solves the problem that the setting time of geopolymers is difficult to control under low and high temperature conditions, so that geopolymer materials can be efficiently constructed under a variety of temperature environments, expanding their application scenarios.
[0030] (2) The present invention optimizes the thermal mitigation effect and volcanic ash effect of the calcium-based material A at high temperatures (25-50°C)
[0031] The construction performance of kaolin polymer materials activated by calcium-based materials can avoid rapid coagulation and reduce thermal shrinkage.
[0032] (3) The present invention utilizes the high hydration heat of calcium-based material B to achieve self-thermal internal curing of kaolin geopolymer materials based on activation of calcium-based materials at low temperatures (5-25°C), thereby promoting the hydration rate of geopolymer materials at low temperatures, shortening the setting time and achieving early strength effects.
[0033] (4) The present invention controls the setting time of the geopolymer through a designed calculation formula, which can prevent the setting from being too slow or the early strength from being too low in a low temperature environment, and prevent the setting from being too fast or the fluidity from being lost in a high temperature environment. This technology ensures that the geopolymer has good construction performance under different construction temperature conditions, which helps to improve construction efficiency and project quality.
[0034] (5) The method of the present invention simplifies the preparation process by reasonable proportioning and temperature control. Compared with the prior art which requires complex curing or cumbersome feeding steps, the present invention provides a more efficient and easily industrialized production process.
[0035] (6) Since the present invention uses geopolymer, a new type of low-carbon material, compared with traditional building materials such as cement, the energy consumption in the production process is reduced. The present invention helps to achieve low-carbon emissions and sustainable development goals in the construction industry.
[0036] (7) The present invention provides a formula for calculating the setting time of geopolymers. By adjusting the ratio of geopolymers, the setting time at different temperatures is controlled, thereby quantitatively correcting the ratio design of geopolymers. This has a certain reference value for the ratio design of geopolymers at different temperatures. DETAILED DESCRIPTION
[0037] In order to make the use method and features of the present invention more obvious and easy to understand, the following embodiments are specifically cited for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.
[0038] In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed, and the value should not be limited to the upper and lower limits or specific examples.
[0039] The present invention discloses a geopolymer capable of accommodating different ambient temperatures and based on activation of calcium-based materials, a preparation method thereof, and a method for regulating the setting time thereof, wherein the geopolymer material comprises metakaolin, an alkali activator, a calcium-based material A, and a calcium-based material B:
[0040] Calculated by weight percentage, 40-50% of metakaolin, 42-50% of alkali activator, 2-8% of calcium-based material A, and 2-15% of calcium-based material B, the sum of the weight percentages of each raw material is 100%;
[0041] When used, the preparation is carried out according to the following steps: (1) preparing sodium hydroxide solution: mixing solid sodium hydroxide and water, stirring until a uniform transparent solution is obtained, and the solution temperature is cooled to room temperature before use; (2) preparing an alkali activator: mixing liquid water glass with the sodium hydroxide solution prepared in (1) in proportion and stirring evenly to obtain an alkali activator; (3) preparing a geopolymer slurry: pouring metakaolin, calcium-based material A and calcium-based material B into a cement slurry mixer, stirring at a low speed for 30 seconds, and at the same time slowly and uniformly pouring in the alkali activator, stirring for 15-30 seconds until the mixture is uniform, and continuing to stir at a high speed for 60 seconds to obtain a geopolymer slurry; (4) molding and curing: pouring the geopolymer slurry prepared in (3) into a mold, vibrating on a vibration platform for 60 seconds, and placing it in a specified temperature environment for curing for 24 hours, thereby obtaining a geopolymer activated based on the calcium-based material, wherein the specified temperature is the ambient temperature during actual application, i.e., 5-50°C.
[0042] Furthermore, the mesh size of the metakaolin is not less than 1250 meshes.
[0043] Furthermore, the alkaline activator comprises, by weight percentage, 70-72% of liquid water glass, 12-14% of solid sodium hydroxide and 16-18% of water, and the alkaline activator modulus prepared by using solid sodium hydroxide is 1.4-1.6.
[0044] Furthermore, the calcium-based material A is high-calcium fly ash.
[0045] Furthermore, the calcium-based material B is calcium oxide.
[0046] Furthermore, the water glass is liquid water glass with a modulus of 3.1-3.3 and a solid content of 42.5%.
[0047] To make the contents of the present invention easier to understand, the technical solutions of the present invention are further described below in conjunction with specific implementation examples, but the present invention is not limited thereto. Each example is prepared according to the above laboratory method.
[0048] The raw materials used in each example: metakaolin, high calcium fly ash and liquid water glass, the composition content is shown in Table 1:
[0049]
[0050] Example 1
[0051] A method for controlling the setting time of geopolymers based on activation of calcium-based materials and capable of facing different ambient temperatures
[0052] By weight percentage, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water are mixed to prepare the alkali activator. By weight percentage, 46% of metakaolin, 50% of alkali activator, 2% of calcium-based material A and 2% of calcium-based material B are mixed to prepare the geopolymer. The basic parameters and the calculated values and laboratory values of the setting time are as shown in the following table;
[0053] Since the setting time was not within the appropriate range (initial setting time was greater than 180 min), adjustments were made. After the adjustment, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water were mixed by weight to prepare the alkali activator. By weight, 40% of metakaolin, 43% of the alkali activator, 2% of the calcium-based material A and 15% of the calcium-based material B were mixed to prepare the geopolymer, and the setting time met the requirements.
[0054]
[0055] Example 2
[0056] A method for controlling the setting time of geopolymers based on activation of calcium-based materials and capable of facing different ambient temperatures
[0057] By weight percentage, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water are mixed to prepare the alkali activator. By weight percentage, 46% of metakaolin, 50% of alkali activator, 2% of calcium-based material A and 2% of calcium-based material B are mixed to prepare the geopolymer. The basic parameters and the calculated values and laboratory values of the setting time are as shown in the following table;
[0058] Since the setting time was not within the appropriate range (the final setting time was less than 120 min), adjustments were made. After the adjustment, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water were mixed by weight to prepare the alkali activator. By weight, 46% of metakaolin, 46% of the alkali activator, 6% of the calcium-based material A and 2% of the calcium-based material B were mixed to prepare the geopolymer, and the setting time met the requirements.
[0059]
[0060] Example 3
[0061] A method for controlling the setting time of geopolymers based on activation of calcium-based materials and capable of facing different ambient temperatures
[0062] By weight percentage, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water are mixed to prepare the alkali activator. By weight percentage, 44% of metakaolin, 49% of alkali activator, 2% of calcium-based material A and 5% of calcium-based material B are mixed to prepare the geopolymer. The basic parameters and the calculated values and laboratory values of the setting time are as shown in the following table;
[0063] The setting time meets the requirements and no adjustment is required.
[0064]
[0065] Example 4
[0066] A method for controlling the setting time of geopolymers based on activation of calcium-based materials and capable of facing different ambient temperatures
[0067] By weight percentage, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water are mixed to prepare the alkali activator. By weight percentage, 48% of metakaolin, 42% of alkali activator, 2% of calcium-based material A and 8% of calcium-based material B are mixed to prepare the geopolymer. The basic parameters and the calculated values and laboratory values of the setting time are as shown in the following table;
[0068] The setting time meets the requirements and no adjustment is required.
[0069]
[0070] Example 5
[0071] A method for controlling the setting time of geopolymers based on activation of calcium-based materials and capable of facing different ambient temperatures
[0072] By weight percentage, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water are mixed to prepare the alkali activator. By weight percentage, 44% of metakaolin, 40% of alkali activator, 2% of calcium-based material A and 2% of calcium-based material B are mixed to prepare the geopolymer. The basic parameters and the calculated values and laboratory values of the setting time are as shown in the following table;
[0073] The setting time meets the requirements and no adjustment is required.
[0074]
[0075] Example 6
[0076] A method for controlling the setting time of geopolymers based on activation of calcium-based materials and capable of facing different ambient temperatures
[0077] By weight percentage, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water are mixed to prepare the alkali activator. By weight percentage, 49% of metakaolin, 47% of alkali activator, 2% of calcium-based material A and 2% of calcium-based material B are mixed to prepare the geopolymer. The basic parameters and the calculated values and laboratory values of the setting time are as shown in the following table;
[0078] Since the setting time was not within the appropriate range (the initial setting time was greater than 180 min, and the final setting time was greater than 360 min), adjustments were made. After the adjustment, 70% of liquid water glass, 13% of solid sodium hydroxide and 17% of water were mixed by weight to prepare the alkali activator. By weight, 42% of metakaolin, 45% of the alkali activator, 2% of the calcium-based material A and 11% of the calcium-based material B were mixed to prepare the geopolymer, and the setting time met the requirements.
[0079]
[0080]
[0081] It can be seen from the above embodiments that the geopolymer prepared by the present invention can face different ambient temperatures and is based on the activation of calcium-based materials. Its applicable ambient temperature range can reach 5-50°C, and it can always maintain good performance within this temperature range; the present invention can quickly solidify under normal temperature conditions; it can utilize the thermal relaxation effect and volcanic ash effect of the calcium-based material A in a high temperature (25-50°C) environment to avoid rapid solidification and reduce thermal shrinkage; it can utilize the high hydration heat of the calcium-based material B in a low temperature (5-25°C) environment to achieve self-heating internal curing, thereby promoting the hydration rate of the geopolymer material at low temperature, shortening the solidification time and achieving early strength effect.
[0082] The present invention provides a formula for calculating the setting time of a geopolymer with optimized ratio, and controls the setting time at different temperatures by adjusting the ratio of the geopolymer, thereby quantitatively correcting the ratio design of the geopolymer, which has a certain reference value for the ratio design of the geopolymer at different ambient temperatures.
Claims
1. A geopolymer based on calcium-based material activation, characterized in that: The geopolymer comprises, by weight percentage, 40-50% of metakaolin, 42-50% of an alkali activator, 2-10% of a calcium-based material A, and 2-8% of a calcium-based material B, and the sum of the weight percentages of the raw materials is 100%; The method for preparing the geopolymer comprises the following steps: 1) Stirring: Pour the metakaolin, calcium-based material A and calcium-based material B into a cement slurry mixer and stir at a low speed, pour the alkali activator during the low-speed stirring, then stir at a low speed until the mixture is uniform, and finally stir at a high speed to obtain a geopolymer slurry; 2) Molding and curing: Pour the geopolymer slurry prepared in step 1) into a mold, vibrate on a vibration platform for 60 seconds, and place in a specified temperature environment for curing for 24 hours to obtain a geopolymer activated based on a calcium-based material.
2. The geopolymer based on calcium-based material activation according to claim 1, characterized in that: The mesh number of the metakaolin is not less than 1250 meshes.
3. The geopolymer based on calcium-based material activation according to claim 1, characterized in that: The alkaline activator comprises, by weight percentage, 70-72% of liquid water glass, 12-14% of solid sodium hydroxide and 16-18% of water, and the alkaline activator modulus prepared by using solid sodium hydroxide is 1.4-1.6; The preparation method of the base activator is: a) preparing sodium hydroxide solution: mixing solid sodium hydroxide and water, stirring until a uniform transparent solution is obtained, and using the solution after the solution temperature drops to room temperature; b) preparing an alkaline activator: mixing liquid water glass and the sodium hydroxide solution prepared in step a) and stirring them uniformly to obtain an alkaline activator.
4. The geopolymer based on calcium-based material activation according to claim 3, characterized in that: The modulus of the liquid water glass is 3.1-3.3, and the solid content is 42.5%.
5. The geopolymer based on calcium-based material activation according to claim 1, characterized in that: The calcium-based material A is high-calcium fly ash, and its components include: SiO2: 45-55wt%, Al2O3: 25-35wt%, CaO: 10-15wt%, and the rest are impurities; the calcium-based material B is one of calcium oxide and cement clinker.
6. The geopolymer based on calcium-based material activation according to claim 1, characterized in that: In step 2), the site temperature environment is 5-50°C.
7. The geopolymer based on calcium-based material activation according to claim 1, characterized in that: In step 1), the stirring speeds of the low-speed stirring and the high-speed stirring are 90-100 r / min and 250-260 r / min respectively.
8. A method for controlling the setting time of a geopolymer based on activation of a calcium-based material according to any one of claims 1 to 7, characterized in that: The method for regulating coagulation time comprises the following steps: Step 1: Based on the selected initial raw material ratio, calculate the molar ratio of Na2O / Al2O3, i.e. According to the site temperature conditions, the average site temperature for 72 hours is obtained as the ambient temperature T; Step 2: Substituting the ambient temperature T and the initial raw material ratio into the geopolymer setting time calculation formula, the setting time of the geopolymer activated by the calcium-based material is calculated, and the setting time includes the initial setting time and the final setting time; Step three: Compare the initial setting time and final setting time calculated in step two with the initial setting time and final setting time required for construction. If they do not meet the construction requirements, adjust the weight percentage of calcium-based material A and calcium-based material B based on the geopolymer setting time calculation formula, correct the setting time, make the setting time meet the construction requirements, and prepare a kaolin geopolymer based on calcium-based material activation suitable for the current ambient temperature T according to the optimized raw material ratio.
9. The method for controlling coagulation time according to claim 8, characterized in that: In step 2, the formula for calculating the setting time of the geopolymer is: Initial setting time: Final setting time: Wherein: CaA is the weight percentage of calcium-based material A; CaB is the weight percentage of calcium-based material B.
10. The method for controlling coagulation time according to claim 8, characterized in that: In step three, the construction requires an initial setting time of 45-120 minutes and a final setting time of 120-360 minutes.
Citation Information
Patent Citations
Metakaolin-slag base geological polymer for oilfield cementing and high temperature retarder thereof
CN101323778A
Geopolymer capable of being rapidly hardened at normal temperature and preparation method of thereof
CN105621911A
Rapid hardening geopolymer based on low-temperature crystallization and preparation method thereof
CN118307245A
Geopolymer heat protection material, and preparation method and spraying process thereof
CN107759150A
Anti-corrosion geopolymer concrete filling pile material as well as preparation method and construction process thereof
CN108675699A